Trends in language assessment and testing: A bibliometric study - Zhang, Xian (Studies in Second Language Learning and Teaching, 2025)
The current bibliometric study employed citation analysis and keyword analysis to perform a review of language assessment and testing. Based on citation counts and keywords, this study identified the recent trends/changes and the most influential regions, institutions, scholars, and publications in the field. In addition, the intellectual structures of the field reviewed by the network maps of the most influential documents and scholars showed how these eminent documents and authors were related to each other. It was found that the field experienced significant changes with the emergence of new scholars, research themes, and topics. This study is also a tribute to hundreds of scholarly documents in the field, which keep the field moving forward.